Investigation of the effect of low back health education on physical function and body awareness in academicians: A randomized controlled study. - Genç, Selen; Cavlak, Uğur (Work, 2026)
Background: Body awareness is a topic, which has been investigating by the scientists, recently. Objective: This study aimed to determine effects of low back health education (BHE) on physical function and body awareness in academicians. Methods: This study is a randomized controlled study. 94 academicians (47 in intervention group and 47 controls) (mean age: 43.22 ± 10.924 years) participated. Participants were evaluated before and after 6-week BHE and exercise program. To evaluate physical functions, One Leg Standing Test, Half Squat, Curl-Up, and Sit and Reach Test were used. The Body Awareness Questionnaire (BAQ) was used to assess body awareness (BA) of participants. Intervention group received BHE, including back school. After the education program, they participated in exercise program (six weeks; one day a week). Control group was only given an informative brochure about BHE. Results: All parameters in terms of physical function increased in both groups (p ≤ 0.05). However, when the groups were compared, difference was found to be significant in favor of intervention group (p ≤ 0.05). BA scores also increased at the end of six weeks in both groups (p ≤ 0.05). But no differences were found between the groups (p ≥ 0.05), except for body response estimation in BAQ (p ≤ 0.05). Conclusions: The results showed that exercise program increased physical functions rather than BA.